Effects of crossbreeding East-Friesian with Awassi ewes on milk production and mammary gland traits - Seker, I; Kul, S; Bayraktar, M; Akcan, A (Polish Soc Veterinary Sciences Editorial Office, 2004)
The study was undertaken to determine first lactation milk production, udder and teat traits and the relation between milk yield and udder/teat traits in Awassi and East-Friesian x Awassi (F-1) ewes. The experimental population was composed of 24 of Awassi and 17 East-Friesian x Awassi (F-1), all of which were at their first lactation. During the lactation period the daily milk production, lactation length, udder height from the ground (UH), udder depth (UD), udder circumference (UC), right teat length (RTL), diameter of the right teat (DRT), teat distance (TD), and udder volume (UV) were determined. The mean daily milk yield, peak daily milk yield, lactation milk yield, and lactation period of crossbreed ewes (0.739 kg, 1.256 kg, 140.8 kg and 190 days) was significantly higher (P<0.05, P<0.01) than that of Awassi ewes (0.677 kg, 0.963 kg, 102.9 kg, and 150 days). Udder height, UD, UC, RTL, DRT, TD, and UV were 28,14.4,40.7,4.2, 2.3, 16.1 cm, and 833.6 ml for Awassi. The corresponding figures for F-1 ewes were 31.2, 16.25, 46.0, 4.29 2.1 cm, 17.8, and 940.0 ml, respectively. The results indicated that milk yield and udder traits were significantly better in F-1 ewes compared to Awassi. In addition, phenotypic correlations between milk yield and UH, TD, and UV were found to be significant.
Keywords: udder-teat traits; milk yield; East-Friesian; Awassi